Magnetic tape and magnetic recording / reproducing device
The magnetic tape with a specific refractive index difference and logarithmic damping rate addresses the issue of increased missing pulses in low temperature and high humidity environments, improving data reproduction reliability.
Patent Information
- Application Number
- JP2024006551
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-03-23
- Filing Date
- 2024-01-19
- Publication Date
- 2025-04-16
- Estimated Expiration
- 2039-03-18
AI Technical Summary
Magnetic tapes experience an increase in the frequency of missing pulses when used in low temperature and high humidity environments, leading to reduced reliability and increased error rates during data reproduction.
A magnetic tape with a magnetic layer containing ferromagnetic powder and a binder on a non-magnetic support, where the absolute difference in refractive indices between the in-plane and thickness directions is between 0.25 and 0.40, and the logarithmic damping rate is 0.050 or less, as determined by pendulum viscoelasticity tests.
The proposed magnetic tape design effectively reduces the frequency of missing pulses in low temperature and high humidity environments, enhancing the reliability and performance of magnetic recording and reproducing devices.
Smart Images

Figure 0007663727000006 
Figure 0007663727000007 
Figure 0007663727000008
Abstract
Description
[Technical field]
[0001] The present invention relates to a magnetic tape and a magnetic recording / reproducing device. [Background technology]
[0002] Magnetic recording media are classified into tape-type and disk-type, and tape-type magnetic recording media, i.e., magnetic tape, are mainly used for data storage. Recording and / or reproducing information on magnetic tape is usually performed by contacting and sliding the surface of the magnetic tape (magnetic layer surface) with a magnetic head (hereinafter also simply referred to as "head"). Magnetic tapes that have a configuration in which a magnetic layer containing ferromagnetic powder and a binder is provided on a non-magnetic support are widely used (see, for example, Patent Document 1). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2005-243162 A Summary of the Invention [Problem to be solved by the invention]
[0004] When reproducing information recorded on a magnetic tape, the more frequently a partial drop in the amplitude of the reproduced signal (called a "missing pulse") occurs, the higher the error rate and the lower the reliability of the magnetic tape. Therefore, in order to provide a magnetic tape that can be used with high reliability, it is desirable to reduce the frequency of occurrence of missing pulses.
[0005] In recent years, magnetic tapes used for data storage purposes are sometimes used in data centers where temperature and humidity are controlled. On the other hand, power saving is required in data centers to reduce costs. In order to save power, it is desirable to relax the temperature and humidity control conditions in data centers or to eliminate the need for control. However, if the temperature and humidity control conditions are relaxed or not controlled at all, it is expected that magnetic tapes will be used in various environments, including low-temperature and high-humidity environments. However, as a result of the inventor's investigation, it has been found that the frequency of occurrence of missing pulses tends to increase in low-temperature and high-humidity environments.
[0006] SUMMARY OF THE PRESENT EMBODIMENT An object of the present invention is to provide a magnetic tape in which the frequency of occurrence of missing pulses in a low-temperature, high-humidity environment is reduced. [Means for solving the problem]
[0007] One aspect of the present invention is A magnetic tape having a magnetic layer containing a ferromagnetic powder and a binder on a non-magnetic support, The absolute value ΔN of the difference between the refractive index Nxy measured in the in-plane direction of the magnetic layer and the refractive index Nz measured in the thickness direction of the magnetic layer is 0.25 or more and 0.40 or less, and a magnetic tape in which the logarithmic decrement of the surface of the magnetic layer determined by a pendulum viscoelasticity test (hereinafter also referred to as the "logarithmic decrement of the magnetic layer" or simply the "logarithmic decrement") is 0.050 or less; Regarding.
[0008] In one embodiment, the difference (Nxy-Nz) between the refractive index Nxy and the refractive index Nz can be 0.25 or more and 0.40 or less.
[0009] In one embodiment, the logarithmic decay rate can be equal to or greater than 0.010 and equal to or less than 0.050.
[0010] In one embodiment, the magnetic tape can have a non-magnetic layer containing a non-magnetic powder and a binder between the non-magnetic support and the magnetic layer.
[0011] In one embodiment, the magnetic tape can have a backcoat layer containing a nonmagnetic powder and a binder on the surface side of the nonmagnetic support opposite to the surface side having the magnetic layer.
[0012] A further aspect of the present invention relates to a magnetic recording / reproducing device including the above magnetic tape and a magnetic head. Effect of the Invention
[0013] According to one aspect of the present invention, it is possible to provide a magnetic tape capable of reducing the frequency of occurrence of missing pulses in a low-temperature, high-humidity environment. Also, according to another aspect of the present invention, it is possible to provide a magnetic recording and reproducing device including the magnetic tape. [Brief description of the drawings]
[0014] [Figure 1] FIG. 2 is an explanatory diagram of a method for measuring a logarithmic decrement. [Diagram 2] FIG. 2 is an explanatory diagram of a method for measuring a logarithmic decrement. [Diagram 3] FIG. 2 is an explanatory diagram of a method for measuring a logarithmic decrement. [Figure 4] 1 shows an example (schematic diagram) of a specific embodiment of a magnetic tape manufacturing process. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] [Magnetic tape] One aspect of the present invention relates to a magnetic tape having a magnetic layer containing a ferromagnetic powder and a binder on a non-magnetic support, wherein the absolute value ΔN of the difference between the refractive index Nxy measured in the in-plane direction of the magnetic layer and the refractive index Nz measured in the thickness direction of the magnetic layer is 0.25 or more and 0.40 or less, and the logarithmic decrement of the surface of the magnetic layer determined by a pendulum viscoelasticity test is 0.050 or less.
[0016] In the present invention and this specification, the term "surface of the magnetic layer" is synonymous with the surface of the magnetic layer of a magnetic tape. In addition, in the present invention and this specification, the term "ferromagnetic powder" refers to an aggregate of multiple ferromagnetic particles. The term "aggregate" is not limited to an embodiment in which the particles constituting the aggregate are in direct contact with each other, but also includes an embodiment in which a binder, additive, etc. is interposed between the particles. The above also applies to various powders such as nonmagnetic powders in the present invention and this specification.
[0017] The method for measuring ΔN and the logarithmic decrement is described below.
[0018] In the present invention and this specification, the absolute value ΔN of the difference between the refractive index Nxy measured in the in-plane direction of the magnetic layer and the refractive index Nz measured in the thickness direction of the magnetic layer is a value determined by the following method. The refractive index in each direction of the magnetic layer is determined by using a two-layer model by spectroscopic ellipsometry. In order to determine the refractive index of the magnetic layer by using a two-layer model by spectroscopic ellipsometry, the value of the refractive index of the portion adjacent to the magnetic layer is used. In the following, an example will be described in which the refractive indexes Nxy and Nz of the magnetic layer are determined for a magnetic tape having a layer structure in which a nonmagnetic layer and a magnetic layer are laminated in this order on a nonmagnetic support. However, the magnetic tape according to one embodiment of the present invention can also be a magnetic tape having a layer structure in which a magnetic layer is directly laminated on a nonmagnetic support without a nonmagnetic layer. For a magnetic tape having such a structure, the refractive index in each direction of the magnetic layer is determined in the same manner as in the following method using a two-layer model of a magnetic layer and a nonmagnetic support. In addition, the incidence angle described below is the incidence angle when the incidence angle in the case of perpendicular incidence is set to 0°. (1) Preparation of the measurement sample For magnetic tapes having a backcoat layer on the surface opposite to the surface having the magnetic layer of the non-magnetic support, the backcoat layer of the measurement sample cut out from the magnetic tape is removed before measurement. The backcoat layer can be removed by a known method such as dissolving the backcoat layer with a solvent. As the solvent, for example, methyl ethyl ketone can be used. However, any solvent can be used as long as it can remove the backcoat layer. The surface of the non-magnetic support after the backcoat layer is removed is roughened by a known method so that reflected light from this surface is not detected in the measurement with an ellipsometer. The roughening can be performed, for example, by polishing the surface of the non-magnetic support after the backcoat layer is removed with sandpaper. For measurement samples cut out from magnetic tapes without a backcoat layer, the surface of the non-magnetic support opposite to the surface having the magnetic layer is roughened. In addition, to measure the refractive index of the non-magnetic layer described below, the magnetic layer is further removed to expose the surface of the non-magnetic layer. In order to measure the refractive index of the non-magnetic support described below, the non-magnetic layer is also removed to expose the surface of the non-magnetic support on the magnetic layer side. The removal of each layer can be performed by a known method, as described for removing the backcoat layer. The longitudinal direction described below refers to the direction that was the longitudinal direction of the magnetic tape when the measurement sample was included in the magnetic tape before being cut out. This point is also true for the other directions described below. (2) Refractive index measurement of the magnetic layer Using an ellipsometer, the magnetic layer surface is irradiated with incident light of 300 μm diameter from the longitudinal direction at angles of incidence of 65°, 70°, and 75°, to measure Δ (phase difference between s-polarized light and p-polarized light) and Ψ (amplitude ratio between s-polarized light and p-polarized light). Measurements are performed by changing the wavelength of the incident light in 1.5 nm increments in the range of 400 to 700 nm, and measurements are obtained for each wavelength. Using the measured values of Δ and Ψ of the magnetic layer at each wavelength, the refractive index of the non-magnetic layer in each direction obtained by the method described below, and the thickness of the magnetic layer, the refractive index of the magnetic layer at each wavelength is calculated using a two-layer model as follows. The 0th layer, which is the substrate of the two-layer model, is the non-magnetic layer, and the 1st layer is the magnetic layer. The two-layer model is created by considering only the reflection at the interfaces between air / magnetic layer and magnetic layer / non-magnetic layer, and assuming that there is no effect of back surface reflection of the non-magnetic layer. The refractive index of the 1st layer that best matches the obtained measured values is determined by fitting using the least squares method. The values at a wavelength of 600 nm obtained from the fitting results are the refractive index Nx of the magnetic layer in the longitudinal direction, and the refractive index Nz of the magnetic layer in the thickness direction measured with incident light from the longitudinal direction. 1 Request. The refractive index of the magnetic layer in the width direction, Ny, and the refractive index of the magnetic layer in the thickness direction, Nz, were measured by incident light from the width direction, as the values at a wavelength of 600 nm obtained from the fitting results, in the same manner as above, except that the direction of incidence of the incident light was the width direction of the magnetic tape. 2 Request. The fitting is performed by the following method. Generally, the complex refractive index is n = η + iκ. Here, η is the real part of the refractive index, κ is the extinction coefficient, and i is an imaginary number. The complex dielectric constant ε = ε1 + iε2 (ε1 and ε2 satisfy the Kramers-Kronig relationship) and ε1 = η 2 -κ 2 , ε2=2ηκ, and Nx and Nz 1 When calculating, the complex dielectric constant of Nx is ε x =ε x 1+iε x 2. Nz 1 The complex dielectric constant of ε z1 =ε z1 1+iε z1 Let's say it's 2. ε x 2 is taken as a Gaussian, and an arbitrary point with a peak position of 5.8 to 5.1 eV and σ of 4 to 3.5 eV is taken as the starting point. A parameter that offsets the dielectric constant is placed outside the measurement wavelength range (400 to 700 nm), and Nx is calculated by least-squares fitting of the measured value. Similarly, ε z1 2 is calculated by setting the peak position at 3.2 to 2.9 eV and σ at 1.5 to 1.2 eV as the starting point, setting the offset parameter, and fitting the measured value with least squares to obtain Nz1 Find Ny and Nz 2 The refractive index Nxy measured in the in-plane direction of the magnetic layer is calculated as "Nxy = (Nx + Ny) / 2". The refractive index Nz measured in the thickness direction of the magnetic layer is calculated as "Nz = (Nz 1 +Nz 2 ) / 2". From the calculated Nxy and Nz, calculate the absolute value of the difference between them, ΔN. (3) Refractive index measurement of non-magnetic layer The refractive index of the non-magnetic layer at a wavelength of 600 nm (refractive index in the longitudinal direction, refractive index in the width direction, refractive index in the thickness direction measured with light incident from the longitudinal direction, and refractive index in the thickness direction measured with light incident from the width direction) is determined in the same manner as above, except for the following points. The wavelength of the incident light is changed in increments of 1.5 nm within the range of 250 to 700 nm. Using a two-layer model of a non-magnetic layer and a non-magnetic support, the 0th layer, which is the substrate of the two-layer model, is the non-magnetic support, and the 1st layer is the non-magnetic layer. The two-layer model is created by considering only the reflections at the interfaces between air / non-magnetic layer and non-magnetic layer / non-magnetic support, and assuming that there is no effect from the back surface reflection of the non-magnetic support. In the fitting, seven peaks (0.6 eV, 2.3 eV, 2.9 eV, 3.6 eV, 4.6 eV, 5.0 eV, 6.0 eV) are assumed in the imaginary part of the complex dielectric constant (ε2), and a parameter that offsets the dielectric constant outside the measurement wavelength range (250 to 700 nm) is placed. (4) Refractive index measurement of non-magnetic support The refractive index at a wavelength of 600 nm of the non-magnetic support used to determine the refractive index of the non-magnetic layer using the two-layer model (refractive index in the longitudinal direction, refractive index in the width direction, refractive index in the thickness direction measured with light incident from the longitudinal direction, and refractive index in the thickness direction measured with light incident from the width direction) is determined in the same manner as the method described above for measuring the refractive index of the magnetic layer, except for the following points. Instead of using a two-layer model, a one-layer model with only surface reflection is used. The fitting is done using the Cauchy model (n=A+B / λ 2, n is the refractive index, A and B are constants determined by fitting, and λ is the wavelength).
[0019] Next, the logarithmic decrement of the magnetic layer will be described. In the present invention and this specification, the logarithmic decrement of the magnetic layer is a value determined by the following method. 1 to 3 are explanatory diagrams of a method for measuring a logarithmic decay rate. Hereinafter, the method for measuring a logarithmic decay rate will be described with reference to these drawings. However, the illustrated embodiments are merely examples and do not limit the present invention in any way. A measurement sample 100 is cut out from the magnetic tape to be measured. The cut-out measurement sample 100 is placed on a substrate 103 on a sample stage 101 in a pendulum viscoelasticity tester with the measurement surface (magnetic layer surface) facing upward, and is fixed with a fixing tape 105 or the like in a state where there are no obvious wrinkles that can be visually confirmed. A cylindrical cylinder edge 104 with a pendulum (diameter 4 mm) having a mass of 13 g is placed on the measurement surface of the measurement sample 100 so that the long axis direction of the cylinder edge is parallel to the longitudinal direction of the measurement sample 100. FIG. 1 shows an example of the state (viewed from above) in which the cylindrical cylinder edge 104 with a pendulum is placed on the measurement surface of the measurement sample 100. In the embodiment shown in FIG. 1, a holder / temperature sensor 102 is installed, and the surface temperature of the substrate 103 can be monitored. However, this configuration is not essential. In the embodiment shown in FIG. 1, the longitudinal direction of the measurement sample 100 is the direction indicated by the arrow in the figure, and is the same direction as the longitudinal direction of the magnetic tape from which the measurement sample is cut out. In addition, a pendulum made of a material (e.g., metal, alloy, etc.) that has the property of being attracted to a magnet is used as the pendulum 107 (see FIG. 2). The surface temperature of the substrate 103 on which the measurement sample 100 is placed is raised to 80° C. at a heating rate of 5° C. / min or less (any heating rate may be used as long as it is 5° C. / min or less), and the pendulum motion is started (initial vibration is induced) by releasing the adhesion between the pendulum 107 and the magnet 106. FIG. 2 shows an example of the state (side view) of the pendulum 107 performing the pendulum motion. In the embodiment shown in FIG. 2, the pendulum motion is started by stopping (switching off) the power supply to the magnet (electromagnet) 106 arranged below the sample stage in the pendulum viscoelasticity tester to release the adhesion, and the pendulum motion is stopped by restarting (switching on) the power supply to the electromagnet to cause the pendulum 107 to be attracted to the magnet 106. During the pendulum motion, as shown in FIG. 2, the pendulum 107 repeats its amplitude. From the results obtained by monitoring the displacement of the pendulum with the displacement sensor 108 while the pendulum repeats its amplitude, a displacement-time curve is obtained in which the displacement is plotted on the vertical axis and the elapsed time is plotted on the horizontal axis. An example of the displacement-time curve is shown in FIG. 3. In FIG. 3, the correspondence between the state of the pendulum 107 and the displacement-time curve is shown in a schematic manner. At a constant measurement interval, rest (adhesion) and pendulum motion are repeated, and a logarithmic decay rate Δ (unitless) is calculated from the following formula using the displacement-time curve obtained at a measurement interval after 10 minutes or more (any time longer than 10 minutes is acceptable), and this value is regarded as the logarithmic decay rate of the magnetic layer surface of the magnetic tape. The adsorption time of one adsorption is 1 second or more (any time longer than 1 second is acceptable), and the interval from the end of adsorption to the start of the next adsorption is 6 seconds or more (any time longer than 6 seconds is acceptable). The measurement interval is the time interval from the start of adsorption to the start of the next adsorption. The humidity of the environment in which the pendulum motion is performed may be any relative humidity within the range of 40 to 70% relative humidity.
[0020]
number
[0021] In the displacement-time curve, the interval from a minimum displacement to a minimum displacement again is defined as one period of the wave. Let n be the number of waves included in the displacement-time curve during the measurement interval, and let An be the difference between the minimum displacement and the maximum displacement in the nth wave. In Figure 3, the interval from a minimum displacement to a minimum displacement again in the nth wave is defined as Pn (for example, P for the first wave). 1 , and for the second, P 2 , and for the third, P 3 The logarithmic decay rate is calculated by taking the difference between the minimum displacement and the maximum displacement that appears after the nth wave (A n+1 In the displacement-time curve shown in Figure 3, 4 ) is also used, but the portion where the pendulum 107 is stationary (attached) after the extremely large displacement is not used to count the number of waves. Also, the portion where the pendulum 107 is stationary (attached) before the extremely large displacement is not used to count the number of waves. Therefore, in the displacement-time curve shown in Figure 3, the number of waves is three (n=3).
[0022] The present inventors speculate as follows about the reason why the frequency of occurrence of missing pulses in the above magnetic tape in a low-temperature, high-humidity environment can be reduced. When reproducing information recorded on a magnetic tape, if the magnetic layer surface is scraped by sliding between the magnetic layer surface and the head, the scraped debris may adhere to the head and become head deposits. The inventors speculate that the cause of the generation of missing pulses in a low-temperature, high-humidity environment is that the friction coefficient during sliding between the magnetic layer surface and the head tends to increase in a low-temperature, high-humidity environment, making the contact state during sliding between the magnetic layer surface and the head unstable, and that the generation of head deposits is one of the causes of the unstable contact state. In regard to the above, the inventor believes that ΔN obtained by the above method can be a value that can be an index of the state of existence of ferromagnetic powder in the surface region of the magnetic layer. It is presumed that this ΔN is a value that is influenced by various factors such as the state of existence of the binder, the density distribution of the ferromagnetic powder, in addition to the orientation state of the ferromagnetic powder in the magnetic layer. And, it is considered that a magnetic layer in which ΔN is set to 0.25 to 0.40 by controlling various factors has a high strength of the magnetic layer surface and is difficult to be scraped by sliding with the head. The inventor presumes that this contributes to suppressing the scraping of the magnetic layer surface and the generation of head adhesion during sliding with the head in a low-temperature, high-humidity environment, and ultimately leads to a reduction in the frequency of occurrence of missing pulses in a low-temperature, high-humidity environment. Furthermore, regarding the logarithmic decay rate, the present inventors speculate as follows. The logarithmic decrement obtained by the above method is considered to be an index of the amount of adhesive components that are released from the magnetic layer surface and are present between the magnetic layer surface and the head when the head and the magnetic layer surface contact and slide. The more adhesive components there are, the higher the adhesion between the magnetic layer surface and the head, and the more unstable the contact state becomes when the magnetic layer surface and the head slide. On the other hand, the logarithmic decrement of the magnetic layer in the above magnetic tape is 0.050 or less, that is, the adhesive components are reduced, which is considered to contribute to smooth sliding between the magnetic layer surface and the head. The inventors speculate that this contributes to stabilizing the contact state when the magnetic layer surface and the head slide, and as a result, leads to reducing the frequency of missing pulses in a low-temperature, high-humidity environment. The details of the adhesive component are not clear. The inventors speculate that the adhesive component may be derived from the resin used as the binder. The details are as follows. As the binder, various resins can be used, as described in detail below. The resin is a polymer (including homopolymers and copolymers) of two or more polymerizable compounds, and usually contains a component whose molecular weight is lower than the average molecular weight (hereinafter referred to as a "low molecular weight binder component"). The inventors speculate that such a low molecular weight binder component is released from the magnetic layer surface when the head slides against the magnetic layer surface and is interposed between the magnetic layer surface and the head. The inventors speculate that the low molecular weight binder component is considered to have adhesiveness, and that the logarithmic decrement obtained by the pendulum viscoelasticity test is an index of the amount of the low molecular weight binder component released from the magnetic layer surface when the magnetic layer surface slides against the head. In one embodiment, the magnetic layer is formed by applying a magnetic layer forming composition containing a hardener in addition to a ferromagnetic powder and a binder directly or through another layer onto a non-magnetic support, and then performing a hardening process. This curing treatment allows the binder and the curing agent to undergo a curing reaction (crosslinking reaction). However, the inventor believes that the low molecular weight binder component has poor reactivity in the curing reaction, although the reason is unclear. Therefore, the inventor speculates that the low molecular weight binder component is difficult to remain in the magnetic layer and is easily separated from the magnetic layer, which may be one of the reasons why the low molecular weight binder component becomes interposed between the magnetic layer surface and the head when the magnetic layer surface slides against the head. However, the above is merely speculation and does not limit the present invention in any way.
[0023] The above magnetic tape will be described in further detail below. In the following, the occurrence frequency of missing pulses in a low-temperature, high-humidity environment will also be referred to simply as the "occurrence frequency of missing pulses."
[0024] <Magnetic layer> (ΔN of magnetic layer) The ΔN of the magnetic layer of the magnetic tape is 0.25 or more and 0.40 or less. As described above, a magnetic layer with a ΔN of 0.25 or more and 0.40 or less is presumed to have a high strength on the surface of the magnetic layer and be difficult to be shaved off by sliding with the head in a low-temperature and high-humidity environment. Therefore, when reproducing the information recorded on the magnetic layer in a low-temperature and high-humidity environment, it is considered that the surface of the magnetic layer is less likely to be shaved off during the sliding between the surface of the magnetic layer and the head. This is presumed to contribute to reducing the occurrence frequency of missing pulses in a low-temperature and high-humidity environment. From the perspective of further reducing the occurrence frequency of missing pulses, it is preferable that ΔN is 0.25 or more and 0.35 or less. Specific embodiments of the means for adjusting ΔN will be described later.
[0025] ΔN is the absolute value of the difference between Nxy and Nz. Nxy is the refractive index measured in the in-plane direction of the magnetic layer, and Nz is the refractive index measured in the thickness direction of the magnetic layer. In one embodiment, Nxy > Nz can be satisfied, and in another embodiment, Nxy < Nz can be satisfied. From the perspective of the electromagnetic conversion characteristics of the magnetic tape, it is preferable that Nxy > Nz. Therefore, it is preferable that the difference (Nxy - Nz) between Nxy and Nz is 0.25 or more and 0.40 or less, and more preferably 0.25 or more and 0.35 or less.
[0026] Various means for adjusting ΔN described above will be described later.
[0027] (Logarithmic decrement) The logarithmic decay rate determined by a pendulum viscoelasticity test on the surface of the magnetic layer of the magnetic tape is 0.050 or less from the viewpoint of reducing the frequency of occurrence of missing pulses in a low-temperature, high-humidity environment. From the viewpoint of further reducing the frequency of occurrence of missing pulses, the logarithmic decay rate is preferably 0.048 or less, more preferably 0.045 or less, and even more preferably 0.040 or less. On the other hand, from the viewpoint of reducing the frequency of occurrence of missing pulses, the lower the logarithmic decay rate, the more preferable it is, so the lower limit is not particularly limited. As an example, the logarithmic decay rate can be, for example, 0.010 or more, or 0.015 or more. However, the logarithmic decay rate may be lower than the above-mentioned values. A specific embodiment of the means for adjusting the logarithmic decay rate will be described later.
[0028] (Ferromagnetic powder) The ferromagnetic powder contained in the magnetic layer can be any ferromagnetic powder that is commonly used in the magnetic layers of various magnetic recording media. It is preferable to use ferromagnetic powder with a small average particle size from the viewpoint of improving the recording density of the magnetic recording medium. From this viewpoint, it is preferable to use ferromagnetic powder with an average particle size of 50 nm or less. On the other hand, from the viewpoint of magnetization stability, the average particle size of the ferromagnetic powder is preferably 5 nm or more, more preferably 10 nm or more.
[0029] A preferred specific example of the ferromagnetic powder is ferromagnetic hexagonal ferrite powder. The ferromagnetic hexagonal ferrite powder can be ferromagnetic hexagonal barium ferrite powder, ferromagnetic hexagonal strontium ferrite powder, etc. The average particle size of the ferromagnetic hexagonal ferrite powder is preferably 10 nm or more and 50 nm or less, more preferably 20 nm or more and 50 nm or less, from the viewpoint of improving the recording density and the stability of magnetization. For details of the ferromagnetic hexagonal ferrite powder, for example, refer to paragraphs 0012 to 0030 of JP 2011-225417 A, paragraphs 0134 to 0136 of JP 2011-216149 A, and paragraphs 0013 to 0030 of JP 2012-204726 A.
[0030] A preferred specific example of the ferromagnetic powder is ferromagnetic metal powder. From the viewpoint of improving recording density and magnetization stability, the average particle size of the ferromagnetic metal powder is preferably 10 nm or more and 50 nm or less, more preferably 20 nm or more and 50 nm or less. For details of the ferromagnetic metal powder, refer to, for example, paragraphs 0137 to 0141 of JP 2011-216149 A and paragraphs 0009 to 0023 of JP 2005-251351 A.
[0031] A specific example of a preferred ferromagnetic powder is ε-iron oxide powder. Known methods for producing ε-iron oxide powder include a method of producing it from goethite and a reverse micelle method. All of the above production methods are publicly known. For a method for producing ε-iron oxide powder in which part of Fe is substituted with a substitution atom such as Ga, Co, Ti, Al, or Rh, see, for example, J. Jpn. Soc. Powder Metallurgy Vol. 61 Supplement, No. S1, pp. S280-S284 and J. Mater. Chem. C, 2013, 1, pp.5200-5206. However, the method for producing ε-iron oxide powder that can be used as the ferromagnetic powder in the magnetic layer is not limited.
[0032] In the present invention and this specification, unless otherwise specified, the average particle size of various powders such as ferromagnetic powders is a value measured by the following method using a transmission electron microscope. The powder is photographed at a magnification of 100,000 times using a transmission electron microscope, and then printed on photographic paper at a total magnification of 500,000 times to obtain a photograph of the particles that make up the powder. From the obtained particle photograph, the target particle is selected, the particle's outline is traced with a digitizer, and the particle (primary particle) size is measured. Primary particles are independent particles that are not aggregated. The above measurements are carried out for 500 randomly selected particles. The arithmetic mean of the particle sizes of the 500 particles thus obtained is taken as the average particle size of the powder. As the transmission electron microscope, for example, a Hitachi transmission electron microscope H-9000 type can be used. The particle size can be measured using known image analysis software, for example, Carl Zeiss image analysis software KS-400. Values related to the size of the powder, such as the average particle size, shown in the examples below are values measured using a Hitachi transmission electron microscope H-9000 type as the transmission electron microscope and Carl Zeiss image analysis software KS-400 as the image analysis software, unless otherwise specified.
[0033] As a method for collecting a sample powder from a magnetic recording medium for particle size measurement, for example, the method described in paragraph 0015 of JP 2011-048878 A can be used.
[0034] In the present invention and this specification, unless otherwise specified, the size of the particles constituting the powder (particle size) is determined by the shape of the particles observed in the particle photograph. (1) In the case of needle-shaped, spindle-shaped, columnar (where the height is greater than the maximum major axis of the base), etc., it is expressed by the length of the major axis that constitutes the particle, i.e., the major axis length. (2) In the case of a plate or columnar shape (where the thickness or height is smaller than the maximum long diameter of the plate or base), it shall be expressed by the maximum long diameter of the plate or base. (3) In the case of a particle having a spherical, polyhedral, or unspecified shape, and the major axis of the particle cannot be specified from its shape, the particle is expressed as the equivalent circle diameter, which is determined by the circle projection method.
[0035] The average acicular ratio of a powder refers to the arithmetic average of the short axis length of the particles, i.e., the short axis length, the (long axis length / short axis length) value of each particle, and the values obtained for the 500 particles. Here, unless otherwise specified, the short axis length refers to the length of the short axis constituting the particle in the above definition of particle size (1), and to the thickness or height in the above definition of particle size (2), and in the above definition of particle size (3), since there is no distinction between the long axis and the short axis, (long axis length / short axis length) is considered to be 1 for the sake of convenience. Unless otherwise specified, when the particle shape is specific, for example, in the case of the above definition of particle size (1), the average particle size is the average major axis length, in the case of definition (2), the average particle size is the average plate diameter, and in the case of definition (3), the average particle size is the average diameter (also called the average particle diameter or average particle size).
[0036] In one embodiment, the shape of the ferromagnetic particles constituting the ferromagnetic powder contained in the magnetic layer can be plate-like. Hereinafter, ferromagnetic powder composed of plate-like ferromagnetic particles will be referred to as plate-like ferromagnetic powder. The average plate ratio of the plate-like ferromagnetic powder can preferably be in the range of 2.5 to 5.0. The average plate ratio is the arithmetic mean of (maximum major axis / thickness or height) in the case of the above definition (2). The larger the average plate ratio, the more likely it is that the uniformity of the orientation state of the ferromagnetic particles constituting the plate-like ferromagnetic powder will be improved by the orientation treatment, and the value of ΔN will tend to be larger.
[0037] The activation volume can also be used as an index of the particle size of the ferromagnetic powder. "Activation volume" is a unit of magnetization reversal. The activation volume described in this invention and this specification is a value obtained by measuring the coercive force Hc using a vibration sample magnetometer at a magnetic field sweep speed of 3 minutes and 30 minutes in an environment of an atmospheric temperature of 23°C ± 1°C, and by using the following relationship between Hc and activation volume V. The activation volume shown in the examples described later is a value obtained by measuring using a vibration sample magnetometer manufactured by Toei Kogyo Co., Ltd. Hc=2Ku / Ms{1-[(kT / KuV)ln(At / 0.693)] 1 / 2} [In the above formula, Ku: anisotropy constant, Ms: saturation magnetization, k: Boltzmann constant, T: absolute temperature, V: activation volume, A: spin precession frequency, t: magnetic field reversal time] From the viewpoint of improving recording density, the activation volume of the ferromagnetic powder is 2500 nm 3 Preferably, it is 2300 nm or less. 3 More preferably, it is 2000 nm or less. 3 On the other hand, from the viewpoint of magnetization stability, the activation volume of the ferromagnetic powder is, for example, 800 nm 3 It is preferable that the thickness is 1000 nm or more. 3 More preferably, it is 1200 nm or more. 3 More preferably, it is equal to or greater than this.
[0038] The content (filling rate) of the ferromagnetic powder in the magnetic layer is preferably in the range of 50 to 90% by mass, more preferably in the range of 60 to 90% by mass. The components of the magnetic layer other than the ferromagnetic powder are at least one or more components selected from the group consisting of fatty acids and fatty acid amides, and a binder, and may optionally contain one or more further additives. A high filling rate of the ferromagnetic powder in the magnetic layer is preferable from the viewpoint of improving recording density.
[0039] (Binding agent, hardener) The magnetic tape is a coating type magnetic tape, and contains a binder in the magnetic layer. The binder is one or more kinds of resin. The resin may be a homopolymer or a copolymer. The binder contained in the magnetic layer may be selected from polyurethane resin, polyester resin, polyamide resin, vinyl chloride resin, acrylic resin copolymerized with styrene, acrylonitrile, methyl methacrylate, etc., cellulose resin such as nitrocellulose, epoxy resin, phenoxy resin, polyvinyl acetal, polyvinyl butyral, etc., and may be used alone or in combination of a plurality of resins. Among these, polyurethane resin, acrylic resin, cellulose resin, and vinyl chloride resin are preferred. These resins may also be used as binders in the non-magnetic layer and / or backcoat layer described later. For the above binders, refer to paragraphs 0029 to 0031 of JP 2010-24113 A. The average molecular weight of the resin used as the binder may be, for example, 10,000 or more and 200,000 or less in weight average molecular weight. The weight average molecular weight in the present invention and this specification is a value obtained by converting a value measured by gel permeation chromatography (GPC) into polystyrene equivalent. The measurement conditions include the following conditions. The weight average molecular weight shown in the examples described later is a value obtained by converting a value measured under the following measurement conditions into polystyrene equivalent. GPC equipment: HLC-8120 (Tosoh Corporation) Column: TSK gel Multipore HXL-M (Tosoh Corporation, 7.8 mm ID (inner diameter) × 30.0 cm) Eluent: tetrahydrofuran (THF)
[0040] In one embodiment, a binder containing an acidic group can be used as the binder. In the present invention and the present specification, an acidic group is a group that reacts with H in water or a solvent containing water (aqueous solvent). +The term "acidic group" is used to include groups capable of releasing an anion and dissociating into an anion, and their salt forms. Specific examples of acidic groups include sulfonic acid groups, sulfate groups, carboxy groups, phosphoric acid groups, and their salt forms. For example, a sulfonic acid group (-SO 3 H) The salt form is -SO 3 M means a group representing an atom (e.g., an alkali metal atom) that can become a cation in water or an aqueous solvent. This also applies to the salt forms of the above various groups. An example of a binder containing an acidic group can be, for example, a resin containing at least one acidic group selected from the group consisting of a sulfonic acid group and its salts (e.g., polyurethane resin, vinyl chloride resin, etc.). However, the resin contained in the magnetic layer is not limited to these resins. In addition, in a binder containing an acidic group, the amount of acidic groups can be in the range of, for example, 20 to 500 eq / ton. Note that eq is an equivalent weight, and is a unit that cannot be converted into SI units. The content of various functional groups such as acidic groups contained in the resin can be determined by a known method depending on the type of functional group. The value of ΔN tends to be larger as the amount of acidic groups increases when a binder with a larger amount of acidic groups is used. The binder can be used in the magnetic layer forming composition in an amount of, for example, 1.0 to 30.0 parts by mass, preferably 1.0 to 20.0 parts by mass, relative to 100.0 parts by mass of the ferromagnetic powder. The more the amount of binder used relative to the ferromagnetic powder, the larger the ΔN value tends to be.
[0041] A curing agent can also be used together with the resin usable as a binder. In one embodiment, the curing agent can be a thermosetting compound that undergoes a curing reaction (crosslinking reaction) by heating, and in another embodiment, the curing agent can be a photocuring compound that undergoes a curing reaction (crosslinking reaction) by irradiation with light. The curing agent can be included in the magnetic layer in a state where at least a part of the curing agent reacts (crosslinks) with other components such as the binder as the curing reaction proceeds during the magnetic layer forming process. This point is also true for layers formed using a composition used to form other layers that contains a curing agent. A preferred curing agent is a thermosetting compound, and polyisocyanate is suitable. For details about polyisocyanate, refer to paragraphs 0124 to 0125 of JP 2011-216149 A. The curing agent can be used in an amount of, for example, 0 to 80.0 parts by mass relative to 100.0 parts by mass of the binder, and preferably 50.0 to 80.0 parts by mass from the viewpoint of improving the strength of the magnetic layer.
[0042] (Additives) The magnetic layer contains a ferromagnetic powder and a binder, and may contain one or more additives as necessary. An example of the additive is the above-mentioned curing agent. In addition, examples of additives contained in the magnetic layer include non-magnetic powders (e.g., inorganic powders, carbon black, etc.), lubricants, dispersants, dispersion aids, antifungal agents, antistatic agents, antioxidants, etc. In addition, examples of non-magnetic powders include non-magnetic powders that can function as abrasives, and non-magnetic powders (e.g., non-magnetic colloidal particles, etc.) that can function as protrusion-forming agents that form protrusions that protrude appropriately on the magnetic layer surface. The average particle size of colloidal silica (silica colloidal particles) shown in the examples described below is a value obtained by the method described as the method for measuring the average particle size in paragraph 0015 of JP-A-2011-048878. The additives can be appropriately selected from commercially available products according to the desired properties, or can be manufactured by a known method, and can be used in any amount. As an example of an additive that can be used in the magnetic layer containing an abrasive, the dispersant described in paragraphs 0012 to 0022 of JP 2013-131285 A can be mentioned as a dispersant for improving the dispersibility of the abrasive. For example, for the lubricant, refer to paragraphs 0030 to 0033, 0035 and 0036 of JP 2016-126817 A. The non-magnetic layer may contain a lubricant. For the lubricant that can be contained in the non-magnetic layer, refer to paragraphs 0030, 0031, 0034, 0035 and 0036 of JP 2016-126817 A. For the dispersant, refer to paragraphs 0061 and 0071 of JP 2012-133837 A. The dispersant may be contained in the non-magnetic layer. For details about dispersants that can be contained in the nonmagnetic layer, reference can be made to paragraph 0061 of JP-A-2012-133837.
[0043] The magnetic layer described above can be provided directly on the surface of the non-magnetic support, or indirectly via a non-magnetic layer.
[0044] <Nonmagnetic layer> Next, the non-magnetic layer will be described. The magnetic tape may have a magnetic layer directly on the surface of the nonmagnetic support, or may have a nonmagnetic layer containing a nonmagnetic powder and a binder between the nonmagnetic support and the magnetic layer. The nonmagnetic powder contained in the nonmagnetic layer may be an inorganic powder or an organic powder. Carbon black or the like may also be used. Examples of inorganic powders include powders of metals, metal oxides, metal carbonates, metal sulfates, metal nitrides, metal carbides, metal sulfides, and the like. These nonmagnetic powders are commercially available, and can also be produced by known methods. For details, refer to paragraphs 0036 to 0039 of JP-A-2010-24113. The content (filling rate) of the nonmagnetic powder in the nonmagnetic layer is preferably in the range of 50 to 90% by mass, more preferably in the range of 60 to 90% by mass.
[0045] For other details of the binder, additives, etc. of the nonmagnetic layer, known techniques related to nonmagnetic layers can be applied. Furthermore, for example, for the type and content of the binder, and the type and content of the additives, known techniques related to magnetic layers can also be applied.
[0046] The nonmagnetic layer in the present invention and this specification also includes a substantially nonmagnetic layer that contains a small amount of ferromagnetic powder, for example as an impurity or intentionally, along with the nonmagnetic powder. A substantially nonmagnetic layer here refers to a layer having a residual magnetic flux density of 10 mT or less, a coercive force of 7.96 kA / m (100 Oe) or less, or a layer having a residual magnetic flux density of 10 mT or less and a coercive force of 7.96 kA / m (100 Oe) or less. It is preferable that the nonmagnetic layer has no residual magnetic flux density or coercive force.
[0047] <Nonmagnetic support> Next, the non-magnetic support (hereinafter, simply referred to as "support") will be described. Examples of the non-magnetic support include known biaxially stretched polyethylene terephthalate, polyethylene naphthalate, polyamide, polyamideimide, aromatic polyamide, etc. Among these, polyethylene terephthalate, polyethylene naphthalate, and polyamide are preferred. These supports may be previously subjected to corona discharge, plasma treatment, easy-adhesion treatment, heat treatment, etc.
[0048] <Backcoat layer> The magnetic tape may also have a backcoat layer containing a nonmagnetic powder and a binder on the surface side opposite to the surface side having the magnetic layer of the nonmagnetic support. The backcoat layer preferably contains one or both of carbon black and inorganic powder. For the binder contained in the backcoat layer and various additives that may be optionally contained, known techniques related to the backcoat layer can be applied, and known techniques related to the formulation of the magnetic layer and / or the nonmagnetic layer can also be applied. For example, the descriptions of paragraphs 0018 to 0020 of JP 2006-331625 A and US Pat. No. 7,029,774, column 4, line 65 to column 5, line 38 can be referred to for the backcoat layer.
[0049] <Various thicknesses> The thickness of the non-magnetic support and each layer in the magnetic tape will be described below. The thickness of the nonmagnetic support is, for example, 3.0 to 80.0 μm, preferably 3.0 to 50.0 μm, and more preferably 3.0 to 10.0 μm.
[0050] The thickness of the magnetic layer can be optimized according to the saturation magnetization of the magnetic head used, the head gap length, the band of the recording signal, etc. The thickness of the magnetic layer is generally 10 nm to 100 nm, and from the viewpoint of high density recording, it is preferably 20 to 90 nm, and more preferably 30 to 70 nm. There is at least one magnetic layer, and the magnetic layer may be separated into two or more layers having different magnetic properties, and a known configuration related to a multilayer magnetic layer can be applied. When the magnetic layer is separated into two or more layers, the thickness of the magnetic layer is the total thickness of these layers.
[0051] The thickness of the nonmagnetic layer is, for example, 0.1 to 1.5 μm, and preferably 0.1 to 1.0 μm.
[0052] The thickness of the backcoat layer is preferably 0.9 μm or less, and more preferably 0.1 to 0.7 μm.
[0053] The thickness of each layer and the non-magnetic support is determined by exposing a cross section of the magnetic tape in the thickness direction by a known method such as an ion beam or a microtome, and then observing the exposed cross section with a scanning transmission electron microscope (STEM). For specific examples of thickness measurement methods, see the description of the thickness measurement method in the Examples below.
[0054] <Manufacturing process> (Preparation of compositions for forming each layer) The process of preparing a composition for forming a magnetic layer, a non-magnetic layer, or a backcoat layer usually includes at least a kneading process, a dispersion process, and a mixing process provided before or after these processes as necessary. Each process may be divided into two or more stages. The components used in the preparation of each layer-forming composition may be added at the beginning or during any process. As the solvent, one or more of various solvents usually used in the manufacture of coating-type magnetic recording media may be used. For the solvent, refer to paragraph 0153 of JP-A-2011-216149. Also, each component may be added in two or more steps in a divided manner. For example, the binder may be added in a divided manner in the kneading process, the dispersion process, and the mixing process for adjusting the viscosity after dispersion. In order to manufacture the above magnetic tape, conventional known manufacturing techniques may be used in various steps. In the kneading process, it is preferable to use a kneader with a strong kneading force, such as an open kneader, a continuous kneader, a pressure kneader, or an extruder. For details of these kneading processes, refer to JP-A-1-106338 and JP-A-1-79274. A known dispersing machine can be used. The ferromagnetic powder and the abrasive can also be dispersed separately. More specifically, the separate dispersion is a method of preparing a composition for forming a magnetic layer through a process of mixing an abrasive liquid (but substantially not containing ferromagnetic powder) containing an abrasive and a solvent with a magnetic liquid containing a ferromagnetic powder, a solvent and a binder. The above "substantially not containing ferromagnetic powder" means that ferromagnetic powder is not added as a component of the abrasive liquid, and it is acceptable that a small amount of ferromagnetic powder is present as an unintentionally mixed impurity. Regarding ΔN, the longer the dispersion time of the magnetic liquid, the larger the value of ΔN tends to be. This is thought to be because the longer the dispersion time of the magnetic liquid, the higher the dispersibility of the ferromagnetic powder in the coating layer of the composition for forming a magnetic layer, and the more likely it is that the uniformity of the orientation state of the ferromagnetic particles constituting the ferromagnetic powder is improved by the orientation process. Furthermore, the longer the dispersion time when the various components of the nonmagnetic layer-forming composition are mixed and dispersed, the larger the ΔN value tends to be. The dispersion time of the magnetic liquid and the dispersion time of the nonmagnetic layer-forming composition should be set so as to achieve a ΔN of 0.25 or more and 0.40 or less. At any stage of preparing each layer-forming composition, filtration may be performed by a known method. Filtration can be performed, for example, by filter filtration. The filter used for filtration may be, for example, a filter with a pore size of 0.01 to 3 μm (for example, a glass fiber filter, a polypropylene filter, etc.).
[0055] (coating process) The non-magnetic layer and the magnetic layer can be formed by sequentially or simultaneously applying the non-magnetic layer forming composition and the magnetic layer forming composition in a multi-layer manner. The backcoat layer can be formed by applying the backcoat layer forming composition to the surface of the non-magnetic support opposite to the surface having the non-magnetic layer and the magnetic layer (or the non-magnetic layer and / or the magnetic layer will be provided later). The application process for forming each layer can also be performed in two or more steps. For example, in one embodiment, the magnetic layer forming composition can be applied in two or more steps. In this case, a drying process may or may not be performed between the two application steps. An orientation process may or may not be performed between the two application steps. For details of the application for forming each layer, refer to paragraph 0066 of JP 2010-231843 A. Also, a known technique can be applied to the drying process after applying each layer forming composition. With regard to the magnetic layer-forming composition, the lower the drying temperature of the coating layer formed by applying the magnetic layer-forming composition (hereinafter also referred to as the "coating layer of the magnetic layer-forming composition" or simply the "coating layer"), the larger the ΔN value tends to be. The drying temperature can be, for example, the atmospheric temperature at which the drying step is carried out, and may be set so as to achieve a ΔN of 0.25 or more and 0.40 or less.
[0056] (Other processes) Other steps for manufacturing the magnetic tape can be performed using known techniques, and for the various steps, see, for example, paragraphs 0067 to 0070 of JP-A-2010-231843. For example, it is preferable to perform an orientation treatment on the coating layer of the magnetic layer-forming composition while the coating layer is in a wet state. From the viewpoint of the ease of achieving ΔN of 0.25 to 0.40, the orientation treatment is preferably performed by arranging a magnet so that a magnetic field is applied perpendicularly to the surface of the coating layer of the magnetic layer-forming composition (i.e., vertical orientation treatment). The strength of the magnetic field during the orientation treatment may be set so that ΔN of 0.25 to 0.40 can be achieved. In addition, when the coating process of the magnetic layer-forming composition is performed by two or more coating steps, it is preferable to perform the orientation treatment at least after the last coating step, and it is more preferable to perform the vertical orientation treatment. For example, when the magnetic layer is formed by two coating steps, a drying step is performed without performing the orientation treatment after the first coating step, and then the coating layer formed in the second coating step can be subjected to the orientation treatment. It is also preferable to perform calendering at any stage after drying the coating layer of the magnetic layer-forming composition. For the conditions of the calendering, see, for example, paragraph 0026 of JP 2010-231843 A. The higher the calendering temperature (surface temperature of the calender roll), the larger the ΔN value tends to be. The calendering temperature may be set so as to achieve a ΔN of 0.25 or more and 0.40 or less.
[0057] (One embodiment of a preferred manufacturing method) In a preferred embodiment, the magnetic layer can be formed through a magnetic layer forming process including a coating step in which a magnetic layer forming composition containing a ferromagnetic powder, a binder, a hardener and a solvent is applied directly or via a non-magnetic layer onto a non-magnetic support to form a coating layer, a heat drying step in which the coating layer is dried by heat treatment, and a hardening step in which the coating layer is hardened. The magnetic layer forming process preferably includes a cooling step in which the coating layer is cooled between the coating step and the heat drying step, and further includes a burnishing step in which the surface of the coating layer is burnished between the heat drying step and the hardening step.
[0058] It is believed that carrying out the cooling step and the burnishing step in the above magnetic layer formation step is a preferable means for making the logarithmic decrement equal to or less than 0.050. It is speculated that the cooling step of cooling the coating layer between the coating step and the heat drying step contributes to localizing the adhesive component described above on the surface and / or the surface layer portion near the surface of the coating layer. This is because cooling the coating layer of the magnetic layer forming composition before the heat drying step makes it easier for the adhesive component to migrate to the surface and / or surface layer portion of the coating layer when the solvent evaporates in the heat drying step. However, the reason is not clear. It is also speculated that the adhesive component can be removed by varnishing the surface of the coating layer in which the adhesive component is localized on the surface and / or surface layer portion. It is speculated that the logarithmic decrement is reduced to 0.050 or less by performing a curing step after removing the adhesive component in this way. However, the above is merely speculation and does not limit the present invention in any way.
[0059] As described above, the magnetic layer forming composition can be applied in a multi-layer coating successively or simultaneously with the non-magnetic layer forming composition. In a preferred embodiment, the magnetic tape can be manufactured by successive multi-layer coating. The manufacturing process including the successive multi-layer coating can be preferably carried out as follows. A non-magnetic layer is formed through a coating process in which a non-magnetic layer forming composition is applied to a non-magnetic support to form a coating layer, and a heat-drying process in which the formed coating layer is dried by heat treatment. Then, a magnetic layer is formed through a coating process in which a magnetic layer forming composition is applied to the formed non-magnetic layer to form a coating layer, and a heat-drying process in which the formed coating layer is dried by heat treatment.
[0060] A specific embodiment of the above-mentioned manufacturing method will be described below with reference to FIG. 4. However, the present invention is not limited to the following specific embodiment. Hereinafter, the coating layer of the magnetic layer-forming composition before the curing treatment is sometimes referred to as the magnetic layer. This also applies to other layers.
[0061] Fig. 4 is a process schematic diagram showing a specific embodiment of a process for producing a magnetic tape having a nonmagnetic layer and a magnetic layer in this order on one side of a nonmagnetic support and a backcoat layer on the other side. In the embodiment shown in Fig. 4, the nonmagnetic support (long film) is continuously wound from the unwinding section to the winding section, and various treatments such as coating, drying, and orientation are performed in each section or zone shown in Fig. 4, so that a nonmagnetic layer and a magnetic layer can be formed by successive multilayer coating on one side of the running nonmagnetic support, and a backcoat layer can be formed on the other side. This production method can be the same as a production method usually performed for producing a coating-type magnetic tape, except that the magnetic layer formation step includes a cooling zone and a burnishing treatment step before the hardening treatment.
[0062] In the first coating section, the nonmagnetic support delivered from the delivery section is coated with a nonmagnetic layer forming composition (a step of applying the nonmagnetic layer forming composition).
[0063] After the above coating step, in the first heat treatment zone, the coating layer of the nonmagnetic layer forming composition formed in the coating step is heated to dry the coating layer (heat drying step). The heat drying step can be performed by passing the nonmagnetic support having the coating layer of the nonmagnetic layer forming composition through a heated atmosphere. The temperature of the heated atmosphere here can be, for example, about 40 to 140°C. However, the temperature is not limited to the above range as long as it is a temperature that can volatilize the solvent and dry the coating layer. In addition, optionally, heated gas may be blown onto the surface of the coating layer. The above points are the same for the heat drying step in the second heat treatment zone and the heat drying step in the third heat treatment zone described later.
[0064] Next, in the second coating section, a magnetic layer-forming composition is coated onto the non-magnetic layer formed by the heat drying step in the first heat treatment zone (magnetic layer-forming composition coating step).
[0065] After the above coating step, the coating layer of the magnetic layer forming composition formed in the coating step is cooled in a cooling zone (cooling step). For example, the cooling step can be performed by passing the non-magnetic support having the above coating layer formed on the non-magnetic layer through a cooling atmosphere. The temperature of the cooling atmosphere can be preferably in the range of -10°C to 0°C, and more preferably in the range of -5°C to 0°C. The time for performing the cooling step (for example, the time from when any part of the coating layer is carried into the cooling zone until it is carried out (hereinafter, also referred to as "residence time")) is not particularly limited. Since the logarithmic decay rate tends to decrease as the residence time is increased, it is preferable to adjust the logarithmic decay rate by performing a preliminary experiment as necessary so as to realize a logarithmic decay rate of 0.050 or less. In the cooling step, cooled gas may be blown onto the surface of the coating layer.
[0066] In the embodiment in which an orientation treatment is then carried out, the ferromagnetic powder in the coating layer of the magnetic layer-forming composition is oriented in the orientation zone while the coating layer is still wet. For the orientation treatment, the above description can also be referred to.
[0067] The coated layer after the orientation treatment is subjected to a heat drying step in the second heat treatment zone.
[0068] Next, in the third coating section, a backcoat layer forming composition is applied to the surface of the non-magnetic support opposite to the surface on which the non-magnetic layer and the magnetic layer are formed, forming a coating layer (a backcoat layer forming composition application step).Then, in the third heat treatment zone, the coating layer is heat treated and dried.
[0069] In this way, a magnetic tape can be obtained that has a magnetic layer on a non-magnetic layer on one side of a non-magnetic support and a backcoat layer on the other side. The magnetic tape obtained here is then subjected to various treatments described below to become a finished magnetic tape.
[0070] The obtained magnetic tape is wound in a winding section and then cut (slit) to the size of the product magnetic tape. The slitting can be performed using a known cutting machine.
[0071] The surface of the magnetic layer of the slit magnetic tape is burnished (burnishing process between the heating and drying process and the hardening process) before undergoing a hardening process (heating, light irradiation, etc.) according to the type of hardener contained in the magnetic layer. It is presumed that this burnishing process can remove the adhesive components that have been cooled in the cooling zone and migrated to the magnetic layer surface and / or the outer layer portion, which leads to the logarithmic decrement being 0.050 or less. However, this is merely a presumption and does not limit the present invention in any way.
[0072] Burnishing is a process in which the surface of the object to be treated is rubbed with a member (for example, an abrasive tape or a grinding tool such as a grinding blade or grinding wheel), and can be carried out in the same manner as known burnishing processes for manufacturing particulate magnetic recording media. However, burnishing has not been carried out in the past at a stage after the cooling step and the heating and drying step and before the hardening step. In contrast, by carrying out the burnishing at the above stage, the logarithmic decrement can be reduced to 0.050 or less.
[0073] The burnishing treatment can be preferably carried out by rubbing (polishing) the surface of the layer to be treated with an abrasive tape and / or rubbing (grinding) the surface of the layer to be treated with an abrasive tool. The abrasive tape may be a commercially available product, or may be prepared by a known method. The abrasive tool may be a known abrasive blade, such as a fixed blade, a diamond wheel, or a rotary blade, or a grinding wheel. A wiping treatment may be performed in which the surface of the layer rubbed with the abrasive tape and / or the abrasive tool is wiped off with a wiping material. For details of the preferred abrasive tape, a grinding tool, the burnishing treatment, and the wiping treatment, refer to paragraphs 0034 to 0048, FIG. 1, and the examples in JP-A-6-52544. The stronger the burnishing treatment, the smaller the value of the logarithmic attenuation rate. The burnishing treatment can be strengthened by using a high-hardness abrasive as the abrasive contained in the abrasive tape, and can be strengthened by increasing the amount of abrasive in the abrasive tape. Moreover, the harder the grinding tool used, the stronger the burnishing effect. Regarding burnishing conditions, the faster the sliding speed between the surface of the layer to be treated and a member (e.g., an abrasive tape or a grinding tool) is, the stronger the burnishing effect. The sliding speed can be increased by increasing either or both of the speed at which the member is moved and the speed at which the magnetic tape to be treated is moved.
[0074] After the burnishing process (burnishing process step), the magnetic layer is subjected to a hardening process. In the embodiment shown in Fig. 4, the magnetic layer is subjected to a surface smoothing process after the burnishing process and before the hardening process. The surface smoothing process is preferably performed by a calendar process.
[0075] Thereafter, the magnetic layer is subjected to a curing treatment according to the type of curing agent contained in this layer (curing step). The curing treatment can be performed by a treatment according to the type of curing agent contained in the above-mentioned coating layer, such as a heating treatment or light irradiation. The curing treatment conditions are not particularly limited, and may be appropriately set according to the formulation of the magnetic layer forming composition, the type of curing agent, the thickness of the magnetic layer, and the like. For example, when the magnetic layer is formed using a magnetic layer forming composition containing polyisocyanate as a curing agent, the curing treatment is preferably a heating treatment. Note that when a curing agent is contained in a layer other than the magnetic layer, the curing reaction of that layer can also be advanced by the curing treatment here. Alternatively, a separate curing step may be provided. Note that a burnishing treatment may be further performed after the curing step.
[0076] In this way, a magnetic tape according to one embodiment of the present invention can be obtained. However, the above manufacturing method is merely an example, and the values of ΔN and the logarithmic decay rate can be controlled to the above ranges by any means capable of adjusting them, and such an embodiment is also included in the present invention. The magnetic tape is usually housed in a magnetic tape cartridge, and the magnetic tape cartridge is mounted on a magnetic recording and reproducing device. When information recorded on the magnetic tape is reproduced by a magnetic recording and reproducing device in a low-temperature and high-humidity environment, the magnetic tape according to one embodiment of the present invention can reduce the frequency of occurrence of missing pulses.
[0077] In the magnetic tape manufactured as described above, a servo pattern can be formed by a known method in order to enable tracking control of the magnetic head in a magnetic recording and reproducing device, control of the running speed of the magnetic tape, etc. "Formation of a servo pattern" can also be called "recording of a servo signal." The formation of a servo pattern will be described below.
[0078] The servo pattern is usually formed along the longitudinal direction of the magnetic tape. Control methods that use servo signals (servo control) include timing-based servo (TBS), amplitude servo, and frequency servo.
[0079] As shown in ECMA (European Computer Manufacturers Association)-319, magnetic tapes (generally called "LTO tapes") conforming to the LTO (Linear Tape-Open) standard employ a timing-based servo system. In this timing-based servo system, a servo pattern is formed by a pair of non-parallel magnetic stripes (also called "servo stripes") arranged continuously in the longitudinal direction of the magnetic tape. As described above, the reason why the servo pattern is formed by a pair of non-parallel magnetic stripes is to inform the servo signal reading element passing over the servo pattern of its passing position. Specifically, the pair of magnetic stripes is formed so that the interval between them changes continuously along the width direction of the magnetic tape, and the servo signal reading element can know the relative position between the servo pattern and the servo signal reading element by reading the interval. This relative position information enables tracking of the data track. For this purpose, a plurality of servo tracks are usually set on the servo pattern along the width direction of the magnetic tape.
[0080] A servo band is made up of a series of servo signals along the length of the magnetic tape. Usually, multiple servo bands are provided on a magnetic tape. For example, there are five servo bands on an LTO tape. The area between two adjacent servo bands is called a data band. A data band is made up of multiple data tracks, and each data track corresponds to one servo track.
[0081] Also, in one embodiment, as shown in JP 2004-318983 A, information indicating the number of the servo band (also called "servo band ID (identification)" or "UDIM (Unique Data Band Identification Method) information") is embedded in each servo band. This servo band ID is recorded by shifting a specific one of a plurality of pairs of servo stripes in the servo band so that its position is displaced relatively in the longitudinal direction of the magnetic tape. Specifically, the way in which a specific one of a plurality of pairs of servo stripes is shifted is changed for each servo band. As a result, the recorded servo band ID is unique for each servo band, so that the servo band can be uniquely identified simply by reading one servo band with a servo signal reading element.
[0082] As a method for uniquely identifying servo bands, there is also a method using the staggered method as specified in ECMA-319. In this staggered method, a group of pairs of non-parallel magnetic stripes (servo stripes) arranged continuously in the longitudinal direction of the magnetic tape are recorded so that they are shifted in the longitudinal direction of the magnetic tape for each servo band. Since the combination of the shift between adjacent servo bands is unique across the entire magnetic tape, it is possible to uniquely identify the servo bands when reading the servo pattern with two servo signal reading elements.
[0083] Also, as specified in ECMA-319, information indicating the longitudinal position of the magnetic tape (also called "LPOS (Longitudinal Position) information") is usually embedded in each servo band. Like UDIM information, this LPOS information is also recorded by shifting the positions of a pair of servo stripes in the longitudinal direction of the magnetic tape. However, unlike UDIM information, the same signal is recorded in each servo band with this LPOS information.
[0084] It is also possible to embed information other than the above UDIM information and LPOS information in the servo bands. In this case, the embedded information may be different for each servo band, such as UDIM information, or may be common to all servo bands, such as LPOS information. Also, methods other than those described above can be used to embed information in the servo bands. For example, a predetermined code may be recorded by thinning out a predetermined pair from a group of pairs of servo stripes.
[0085] The head for forming a servo pattern is called a servo write head. The servo write head has a pair of gaps corresponding to the pair of magnetic stripes, the number of which is equal to the number of servo bands. Usually, a core and a coil are connected to each pair of gaps, and a magnetic field generated in the core can generate a leakage magnetic field in the pair of gaps by supplying a current pulse to the coil. When forming a servo pattern, a magnetic pattern corresponding to the pair of gaps can be transferred to the magnetic tape by inputting a current pulse while running the magnetic tape on the servo write head, thereby forming the servo pattern. The width of each gap can be appropriately set according to the density of the servo pattern to be formed. The width of each gap can be set, for example, to 1 μm or less, 1 to 10 μm, or 10 μm or more.
[0086] Before forming a servo pattern on the magnetic tape, the magnetic tape is usually subjected to a demagnetization (erase) process. This erase process can be performed by applying a uniform magnetic field to the magnetic tape using a direct current magnet or an alternating current magnet. There are two types of erase processes: DC (Direct Current) erase and AC (Alternating Current) erase. AC erase is performed by gradually lowering the strength of the magnetic field applied to the magnetic tape while reversing the direction of the magnetic field. On the other hand, DC erase is performed by applying a unidirectional magnetic field to the magnetic tape. There are two more methods of DC erase. The first method is horizontal DC erase, which applies a unidirectional magnetic field along the longitudinal direction of the magnetic tape. The second method is vertical DC erase, which applies a unidirectional magnetic field along the thickness direction of the magnetic tape. The erase process may be performed on the entire magnetic tape, or may be performed for each servo band of the magnetic tape.
[0087] The direction of the magnetic field of the formed servo pattern is determined according to the direction of erasure. For example, when the magnetic tape is subjected to horizontal DC erasure, the servo pattern is formed so that the direction of the magnetic field is opposite to the direction of erasure. This makes it possible to increase the output of the servo signal obtained by reading the servo pattern. As shown in JP2012-53940A, when the magnetic pattern is transferred to the magnetic tape that has been vertically DC erased using the above gap, the servo signal obtained by reading the formed servo pattern has a unipolar pulse shape. On the other hand, when the magnetic pattern is transferred to the magnetic tape that has been horizontally DC erased using the above gap, the servo signal obtained by reading the formed servo pattern has a bipolar pulse shape.
[0088] [Magnetic recording and playback device] One aspect of the present invention relates to a magnetic recording and reproducing device including the above magnetic tape and a magnetic head.
[0089] In the present invention and this specification, the term "magnetic recording and reproducing device" refers to a device capable of at least one of recording information on a magnetic tape and reproducing information recorded on the magnetic tape. Such a device is generally called a drive. The magnetic head included in the magnetic recording and reproducing device can be a recording head capable of recording information on a magnetic tape, and can also be a reproducing head capable of reproducing information recorded on the magnetic tape. In one aspect, the magnetic recording and reproducing device can include both a recording head and a reproducing head as separate magnetic heads. In another aspect, the magnetic head included in the magnetic recording and reproducing device can have a configuration in which both a recording element and a reproducing element are provided in one magnetic head. As the reproducing head, a magnetic head (MR head) including a magnetoresistive (MR) element capable of reading information recorded on a magnetic tape with good sensitivity as a reproducing element is preferable. As the MR head, various known MR heads can be used. In addition, the magnetic head that records and / or reproduces information may include a servo pattern reading element. Alternatively, the magnetic recording and reproducing device may include a magnetic head (servo head) equipped with a servo pattern reading element as a separate head from the magnetic head that records and / or reproduces information.
[0090] In the magnetic recording and reproducing device, recording of information on the magnetic tape and reproducing of information recorded on the magnetic tape can be performed by contacting and sliding the magnetic head against the surface of the magnetic layer of the magnetic tape. The magnetic recording and reproducing device may include the magnetic tape according to one aspect of the present invention, and publicly known techniques may be applied for the rest.
[0091] The magnetic recording and reproducing device includes the magnetic tape according to one aspect of the present invention. Therefore, when reproducing information recorded on the magnetic tape in a low-temperature, high-humidity environment, the frequency of occurrence of missing pulses can be reduced. In addition, when the magnetic layer surface and the head slide against each other to record information on the magnetic tape in a low-temperature, high-humidity environment, it is also possible to suppress the contact state between the magnetic layer surface and the head from becoming unstable due to head adhesions caused by scraping of the magnetic layer surface. EXAMPLES
[0092] The present invention will be described below based on examples. However, the present invention is not limited to the embodiments shown in the examples. "Parts" and "%" described below are based on mass.
[0093] [Example 1] <Preparation of abrasive liquid> Alpha conversion rate approximately 65%, BET (Brunauer-Emmett-Teller) specific surface area 20m 2 100.0 parts of alumina powder (HIT-80 manufactured by Sumitomo Chemical Co., Ltd.) with a molecular weight of 1.0 g / g was mixed with 3.0 parts of 2,3-dihydroxynaphthalene (manufactured by Tokyo Chemical Industry Co., Ltd.) and 1.0 parts of SO 3 Sodium-containing polyester polyurethane resin (UR-4800 (SO 3 31.3 parts of a 32% solution of zirconia (Na group: 0.08 meq / g) (solvent is a mixed solvent of methyl ethyl ketone and toluene) was mixed with 570.0 parts of a mixed solvent of methyl ethyl ketone and cyclohexanone at a ratio of 1:1 (by mass) and dispersed for 5 hours using a paint shaker in the presence of zirconia beads. After dispersion, the dispersion and the beads were separated using a mesh to obtain an alumina dispersion.
[0094] <Preparation of Magnetic Layer-Forming Composition> (Magnetic liquid) Plate-shaped ferromagnetic hexagonal barium ferrite powder 100.0 parts (Activation volume: 1600 nm 3 , average plate ratio: 3.5) SO 3 Sodium group-containing polyurethane resin See Table 1 (Weight average molecular weight: 70,000, SO 3 Na base amount: see Table 1) Cyclohexanone 150.0 parts Methyl ethyl ketone 150.0 parts (abrasive liquid) 6.0 parts of the alumina dispersion prepared above (Silica sol (protrusion forming liquid)) Colloidal silica (average particle size: 100 nm) 2.0 parts Methyl ethyl ketone 1.4 parts (Other ingredients) Stearic acid 2.0 parts Butyl stearate 2.0 parts Polyisocyanate (Tosoh Corporation, Coronate (registered trademark)) 2.5 parts (Finishing solvent) Cyclohexanone 200.0 parts Methyl ethyl ketone 200.0 parts
[0095] (Preparation method) The magnetic liquid was prepared by dispersing the various components of the magnetic liquid in a batch-type vertical sand mill using beads as a dispersion medium. Zirconia beads (bead diameter: see Table 1) were used as the beads, and the bead dispersion was carried out for the time shown in Table 1 (magnetic liquid bead dispersion time). The magnetic liquid thus obtained, the above-mentioned abrasive liquid, silica sol, other components and finishing additive solvent were mixed and dispersed with beads for 5 minutes, and then treated (ultrasonic dispersion) for 0.5 minutes with a batch-type ultrasonic device (20 kHz, 300 W). Then, filtration was performed using a filter with a pore size of 0.5 μm to prepare a magnetic layer-forming composition.
[0096] <Preparation of composition for forming nonmagnetic layer> Of the various components of the nonmagnetic layer-forming composition below, the components excluding stearic acid, cyclohexanone, and methyl ethyl ketone were bead-dispersed using a batch-type vertical sand mill (dispersion media: zirconia beads (bead diameter: 0.1 mm), dispersion time: see Table 1) to obtain a dispersion. The remaining components were then added to the obtained dispersion and stirred with a dissolver stirrer. The obtained dispersion was then filtered using a filter (pore size 0.5 μm) to prepare a nonmagnetic layer-forming composition.
[0097] Non-magnetic inorganic powder α-iron oxide: 100.0 parts (Average particle size 10 nm, BET specific surface area 75 m 2 / g) Carbon black: 25.0 parts (average particle size 20nm) SO 3 Sodium-containing polyurethane resin: 18.0 parts (Weight average molecular weight 70,000, SO 3 Na group content 0.2meq / g) Stearic acid: 1.0 parts Cyclohexanone: 300.0 parts Methyl ethyl ketone: 300.0 parts
[0098] <Preparation of Composition for Forming Backcoat Layer> Among the various components of the composition for forming a backcoat layer described below, the components other than stearic acid, butyl stearate, polyisocyanate, and cyclohexanone were kneaded and diluted by an open kneader to obtain a mixed solution. Then, the obtained mixed solution was subjected to a dispersion treatment of 12 passes by a horizontal bead mill using zirconia beads with a bead diameter of 1.0 mm, a bead filling rate of 80 volume %, a rotor tip peripheral speed of 10 m / sec, a residence time of 2 minutes per pass, and so on. Then, the remaining components were added to the obtained dispersion solution, and the mixture was stirred by a dissolver stirrer. Next, the obtained dispersion solution was filtered using a filter (pore size: 1.0 μm) to prepare a composition for forming a backcoat layer.
[0099] Non-magnetic inorganic powder: α-iron oxide 80.0 parts Average particle size (average major axis length): 0.15μm Average acicular ratio: 7 BET specific surface area: 52m 2 / g Carbon black 20.0 parts Average particle size: 20nm Vinyl chloride copolymer 13.0 parts Sulfonate group-containing polyurethane resin 6.0 parts Phenylphosphonic acid 3.0 parts Methyl ethyl ketone 155.0 parts Stearic acid 3.0 parts Butyl stearate 3.0 parts Polyisocyanate 5.0 parts Cyclohexanone 355.0 parts
[0100] <Magnetic tape production> A magnetic tape was produced in the specific embodiment shown in Figure 4. More specifically, the procedure was as follows. A polyethylene naphthalate support having a thickness of 5.0 μm was sent out from the sending section, and a composition for forming a nonmagnetic layer was applied to one surface in a first coating section so that the thickness after drying would be 0.7 μm, and the composition was dried in a first heat treatment zone (ambient temperature 100° C.) to form a nonmagnetic layer. Thereafter, in the second coating section, the magnetic layer-forming composition was applied onto the non-magnetic layer so that the thickness after drying would be 50 nm, forming a coating layer. While the formed coating layer was still wet, it was passed through a cooling zone adjusted to an atmospheric temperature of 0°C for the residence time shown in Table 1, to carry out a cooling step. Thereafter, in the orientation zone, a magnetic field of the strength shown in Table 1 was applied perpendicularly to the surface of the coating layer of the magnetic layer-forming composition to carry out a vertical orientation treatment, and then the coating layer was dried in a second heat treatment zone (atmospheric temperature: magnetic layer drying temperature in Table 1) to form a magnetic layer. Then, in a third coating section, a composition for forming a backcoat layer was applied to the surface of the polyethylene naphthalate support opposite to the surface on which the nonmagnetic layer and magnetic layer were formed, to form a coating layer having a thickness of 0.5 μm after drying, and the formed coating layer was dried in a third heat treatment zone (ambient temperature 100° C.) to form a backcoat layer. The magnetic tape thus obtained was slit into a width of 1 / 2 inch (0.0127 meters), and then the magnetic layer surface was burnished and wiped. Burnishing and wiping were performed in a processing apparatus having the configuration shown in FIG. 1 of JP-A-6-52544, using a commercially available polishing tape (manufactured by Fujifilm Corporation, product name MA22000, abrasive: diamond / Cr 2 O 3 The grinding blade was a commercially available sapphire blade (manufactured by Kyocera, width 5 mm, length 35 mm, tip angle 60 degrees), and the wiping material was a commercially available wiping material (trade name WRP736, manufactured by Kuraray Co., Ltd.). The processing conditions were those in Example 12 of JP-A-6-52544. After the above burnishing and wiping treatments, a calendering (surface smoothing) treatment was performed using a calender roll consisting only of a metal roll at a speed of 80 m / min, a linear pressure of 300 kg / cm (294 kN / m), and the calender temperature (surface temperature of the calender roll) shown in Table 1. Thereafter, a heat treatment (hardening treatment) was performed in an atmosphere at 70° C. for 36 hours, and then a servo pattern was formed on the magnetic layer using a commercially available servo writer. In this manner, the magnetic tape of Example 1 was obtained.
[0101] [Example 4, Comparative Examples 1 to 6] A magnetic tape was prepared in the same manner as in Example 1, except that the various items shown in Table 1 were changed as shown in Table 1. In Table 1, in the comparative examples where "No orientation treatment" is written in the "Magnetic layer formation and orientation" column, the magnetic tape was produced without carrying out the orientation treatment on the coating layer of the magnetic layer-forming composition. In the comparative examples in Table 1 where "Not performed" is written in the columns for cooling zone residence time and burnishing before hardening treatment, the magnetic tape was produced by a manufacturing process that did not include a cooling zone in the magnetic layer formation process, and did not perform burnishing or wiping before hardening treatment.
[0102] [Example 2] After forming the non-magnetic layer, a magnetic layer-forming composition was applied onto the surface of the non-magnetic layer so that the thickness after drying was 25 nm to form a first coating layer. This first coating layer was passed through an atmosphere having an atmospheric temperature (magnetic layer drying temperature) shown in Table 1 without the application of a magnetic field to form a first magnetic layer (without orientation treatment). Thereafter, a magnetic layer-forming composition was applied onto the surface of the first magnetic layer so that the thickness after drying was 25 nm to form a second coating layer. While the formed second coating layer was still wet, it was passed through a cooling zone adjusted to an atmospheric temperature of 0° C. for the residence time shown in Table 1 to carry out a cooling process. Thereafter, in the orientation zone, a magnetic field of the intensity shown in Table 1 was applied in the vertical direction to the surface of the second coating layer to carry out a vertical orientation process, and then it was dried in a second heat treatment zone (atmospheric temperature: magnetic layer drying temperature in Table 1) to form a second magnetic layer. A magnetic tape was produced in the same manner as in Example 1, except that a multilayer magnetic layer was formed as described above.
[0103] [Example 3] Magnetic tapes were produced in the same manner as in Example 2, except that the residence time in the cooling zone was changed as shown in Table 1.
[0104] [Comparative Example 7] After the non-magnetic layer was formed, a magnetic layer-forming composition was applied onto the surface of the non-magnetic layer so that the thickness after drying would be 25 nm to form a first coating layer. While this first coating layer was in a wet state, a magnetic field of the strength shown in Table 1 was applied perpendicularly to the surface of the first coating layer using an opposing magnet in an atmosphere having an atmospheric temperature (magnetic layer drying temperature) shown in Table 1, to perform a vertical alignment treatment and a drying treatment, thereby forming a first magnetic layer. Thereafter, a magnetic layer-forming composition was applied onto the surface of the first magnetic layer so as to form a second coating layer with a dry thickness of 25 nm. This second coating layer was passed through an atmosphere having an atmospheric temperature (magnetic layer drying temperature) shown in Table 1 without the application of a magnetic field to form a second magnetic layer (without orientation treatment). A magnetic tape was produced in the same manner as in Comparative Example 2, except that a multilayer magnetic layer was formed as described above.
[0105] [Comparative Example 8] After the non-magnetic layer was formed, a magnetic layer-forming composition was applied onto the surface of the non-magnetic layer so that the thickness after drying would be 25 nm to form a first coating layer. While this first coating layer was in a wet state, a magnetic field of the strength shown in Table 1 was applied perpendicularly to the surface of the first coating layer using an opposing magnet in an atmosphere having an atmospheric temperature (magnetic layer drying temperature) shown in Table 1, to perform a vertical alignment treatment and a drying treatment, thereby forming a first magnetic layer. Thereafter, a magnetic layer-forming composition was applied onto the surface of the first magnetic layer so as to form a second coating layer with a dry thickness of 25 nm. This second coating layer was passed through an atmosphere having an atmospheric temperature (magnetic layer drying temperature) shown in Table 1 without the application of a magnetic field to form a second magnetic layer (without orientation treatment). A magnetic tape was prepared in the same manner as in Comparative Example 6, except that a multilayer magnetic layer was formed as described above, and that the magnetic tape was produced by a manufacturing process that did not include a cooling zone in the magnetic layer formation process and did not perform burnishing or wiping treatments before the hardening treatment.
[0106] [Comparative Example 9] After forming the non-magnetic layer, a magnetic layer-forming composition was applied onto the surface of the non-magnetic layer so that the thickness after drying was 25 nm to form a first coating layer. This first coating layer was passed through an atmosphere having an atmospheric temperature (magnetic layer drying temperature) shown in Table 1 without the application of a magnetic field to form a first magnetic layer (without orientation treatment). Thereafter, a magnetic layer-forming composition was applied onto the surface of the first magnetic layer so that the thickness after drying was 25 nm to form a second coating layer. While this second coating layer was in a wet state, a magnetic field having the strength shown in Table 1 was applied perpendicularly to the surface of the second coating layer using an opposing magnet in an atmosphere having the temperature (magnetic layer drying temperature) shown in Table 1, thereby performing a vertical alignment treatment and a drying treatment to form a second magnetic layer. A magnetic tape was produced in the same manner as in Comparative Example 3, except that a multilayer magnetic layer was formed as described above.
[0107] [Evaluation of magnetic tape properties] (1) Measurement of the logarithmic decrement of the magnetic layer The logarithmic decrement of the magnetic layer of the magnetic tape was determined by the method described above using a rigid pendulum-type physical property tester RPT-3000W (pendulum: brass, substrate: glass substrate, substrate temperature rise rate 5°C / min) manufactured by A&D Co., Ltd. The measurement sample was cut out from the magnetic tape and placed on a glass substrate measuring approximately 3 cm x 5 cm, with four points fixed with fixing tape (Kapton tape manufactured by Toray DuPont) as shown in Figure 1. The adsorption time was 1 second and the measurement interval was 7 to 10 seconds, and a displacement-time curve was created for the 86th measurement interval, and the logarithmic decrement was determined using this curve. The measurement was performed in an environment with a relative humidity of approximately 50%.
[0108] (2) Non-magnetic Support and Thickness of Each Layer The thicknesses of the magnetic layer, nonmagnetic layer, nonmagnetic support, and backcoat layer of each magnetic tape produced were measured by the following method. As a result, in each magnetic tape, the magnetic layer was 50 nm thick, the nonmagnetic layer was 0.7 μm thick, the nonmagnetic support was 5.0 μm thick, and the backcoat layer was 0.5 μm thick. The thicknesses of the magnetic layer, non-magnetic layer and non-magnetic support measured here were used to calculate the refractive indexes described below. (i) Preparation of specimens for cross-sectional observation According to the method described in paragraphs 0193 to 0194 of JP 2016-177851 A, a sample for cross-section observation was prepared including the entire region in the thickness direction from the magnetic layer side surface to the backcoat layer side surface of the magnetic tape. (ii) Thickness measurement The prepared sample was observed by STEM, and a STEM image was taken. This STEM image was a STEM-HAADF (High-Angle Annular Dark Field) image taken at an acceleration voltage of 300 kV and an imaging magnification of 450,000 times, and was taken so that one image included the entire area in the thickness direction from the magnetic layer side surface of the magnetic tape to the backcoat layer side surface. In the STEM image thus obtained, a straight line connecting both ends of the line segment representing the magnetic layer surface was defined as a reference line representing the magnetic layer side surface of the magnetic tape. The straight line connecting both ends of the above line segment is, for example, a straight line connecting the intersection point between the left side of the image (rectangle or square shape) of the STEM image and the above line segment and the intersection point between the right side of the STEM image and the above line segment when the STEM image is taken so that the magnetic layer side of the cross-sectional observation sample is located at the top of the image and the backcoat layer side is located at the bottom. Similarly, a reference line representing the interface between the magnetic layer and non-magnetic layer, a reference line representing the interface between the non-magnetic layer and the non-magnetic support, a reference line representing the interface between the non-magnetic support and the backcoat layer, and a reference line representing the surface of the magnetic tape on the backcoat layer side were defined. The thickness of the magnetic layer was determined as the shortest distance from a randomly selected point on a reference line representing the magnetic layer surface of the magnetic tape to a reference line representing the interface between the magnetic layer and the non-magnetic layer. Similarly, the thicknesses of the non-magnetic layer, non-magnetic support, and backcoat layer were determined.
[0109] (3) ΔN of the magnetic layer In the following, the ellipsometer used was the M-2000U manufactured by Woollam Co., Ltd. The creation and fitting of the two-layer model and the one-layer model were performed using the analysis software WVASE32 manufactured by Woollam Co., Ltd. (i) Measurement of refractive index of non-magnetic support A measurement sample was cut out from each magnetic tape, and the backcoat layer of the measurement sample was wiped off with a cloth soaked in methyl ethyl ketone to expose the surface of the nonmagnetic support. This surface was then roughened with sandpaper so that reflected light from the exposed surface would not be detected in the subsequent measurement using an ellipsometer. The magnetic layer and non-magnetic layer of the measurement sample were then wiped off using a cloth soaked in methyl ethyl ketone, and the roughened surface was attached to the silicon wafer surface using static electricity, so that the measurement sample was placed on the silicon wafer with the non-magnetic support surface exposed by removing the magnetic layer and non-magnetic layer (hereinafter referred to as the "magnetic layer side surface of the non-magnetic support") facing upward. An ellipsometer was used to measure Δ and Ψ by irradiating incident light onto the magnetic layer side surface of the non-magnetic support of the measurement sample on the silicon wafer as described above. Using the measured values and the thickness of the non-magnetic support determined in (2) above, the refractive index of the non-magnetic support (the refractive index in the longitudinal direction, the refractive index in the width direction, the refractive index in the thickness direction measured by irradiating incident light from the longitudinal direction, and the refractive index in the thickness direction measured by irradiating incident light from the width direction) was determined by the method described above. (ii) Measurement of the refractive index of the non-magnetic layer A measurement sample was cut out from each magnetic tape, and the backcoat layer of the measurement sample was wiped off with a cloth soaked in methyl ethyl ketone to expose the surface of the nonmagnetic support. This surface was then roughened with sandpaper so that reflected light from the exposed surface would not be detected in the subsequent measurement using a spectroscopic ellipsometer. Thereafter, the surface of the magnetic layer of the measurement sample was lightly wiped with a cloth soaked in methyl ethyl ketone to remove the magnetic layer and expose the surface of the non-magnetic layer, and then the measurement sample was placed on a silicon wafer in the same manner as in (i) above. The surface of the nonmagnetic layer of the measurement sample on this silicon wafer was measured using an ellipsometer, and the refractive index of the nonmagnetic layer (refractive index in the longitudinal direction, refractive index in the width direction, refractive index in the thickness direction measured with incident light from the longitudinal direction, and refractive index in the thickness direction measured with incident light from the width direction) was determined by spectroscopic ellipsometry using the method described above. (iii) Refractive index measurement of the magnetic layer A measurement sample was cut out from each magnetic tape, and the backcoat layer of the measurement sample was wiped off with a cloth soaked in methyl ethyl ketone to expose the surface of the nonmagnetic support. This surface was then roughened with sandpaper so that reflected light from the exposed surface would not be detected in the subsequent measurement using a spectroscopic ellipsometer. Thereafter, the measurement sample was placed on a silicon wafer in the same manner as in (i) above. The surface of the magnetic layer of the measurement sample on the silicon wafer was measured using an ellipsometer, and the refractive index of the magnetic layer (refractive index in the longitudinal direction Nx, refractive index in the width direction Ny, refractive index in the thickness direction Nz measured by irradiating incident light from the longitudinal direction) was measured by the method described above using spectroscopic ellipsometry. 1 , and the refractive index Nz in the thickness direction measured by incident light from the width direction 2 ) was obtained. From the obtained values, Nxy and Nz were obtained, and further, the absolute value of the difference between them, ΔN, was obtained. For both the magnetic tapes of the examples and the comparative examples, the obtained Nxy was a value larger than Nz (i.e., Nxy>Nz).
[0110] (4) Vertical squareness ratio (SQ) The perpendicular squareness of the magnetic tape is the squareness measured in the perpendicular direction of the magnetic tape. The "perpendicular direction" described in relation to the squareness refers to the direction perpendicular to the surface of the magnetic layer. For each magnetic tape of the examples and comparative examples, the perpendicular squareness was obtained by sweeping the external magnetic field of the magnetic tape at a maximum external magnetic field of 1194 kA / m (15 kOe) and a scan speed of 4.8 kA / m / sec (60 Oe / sec) using a vibration sample magnetometer (manufactured by Toei Kogyo Co., Ltd.) at a measurement temperature of 23°C ± 1°C. The measured value is a value after demagnetization field correction, and is obtained by subtracting the magnetization of the sample probe of the vibration sample magnetometer as background noise. In one embodiment, the perpendicular squareness of the magnetic tape is preferably 0.60 to 1.00, more preferably 0.65 to 1.00. Also, in one embodiment, the perpendicular squareness of the magnetic tape can be, for example, 0.90 or less, 0.85 or less, or 0.80 or less, or can exceed these values.
[0111] [Frequency of missing pulses occurring in low temperature and high humidity environments] The following measurements were carried out in a low-temperature, high-humidity environment at a temperature of 13° C. and a relative humidity of 80%. The magnetic tape cartridges containing each of the magnetic tapes of the Examples and Comparative Examples (total length of magnetic tape: 500 m) were set in an IBM LTO-G6 (Linear Tape-Open Generation 6) drive, and the magnetic tape was run 1,500 times back and forth at a tension of 0.6 N and a running speed of 8 m / sec. The magnetic tape cartridge after the above running was set in a reference drive (IBM LTO-G6 drive), and the magnetic tape was run to perform recording and playback. The playback signal during running was input to an external AD (Analog / Digital) conversion device, and a signal where the playback signal amplitude was 70% or more lower than the average (average of the measured values for all tracks) was defined as a missing pulse, and the frequency of occurrence (number of occurrences) was divided by the total length of the magnetic tape to obtain the missing pulse occurrence frequency (unit: times / m) per unit length (per 1m) of the magnetic tape. If the missing pulse occurrence frequency is 5 times / m or less, the magnetic tape can be judged to be highly reliable for practical use.
[0112] The above results are shown in Table 1 (Table 1-1 to Table 1-4).
[0113] [Table 1-1]
[0114] [Table 1-2]
[0115] [Table 1-3]
[0116] [Table 1-4]
[0117] From the results shown in Table 1, it can be seen that the magnetic tapes of Examples 1 to 4, in which the ΔN and logarithmic decrement of the magnetic layer are within the ranges described above, have a reduced frequency of missing pulse occurrence in a low-temperature, high-humidity environment compared to the magnetic tapes of Comparative Examples 1 to 9. Generally, the squareness ratio is known as an index of the state of existence of ferromagnetic powder in the magnetic layer. However, as shown in Table 1, even if the magnetic tapes have the same perpendicular squareness ratio, ΔN is different (for example, Example 1 and Comparative Example 8). The inventor believes that this indicates that ΔN is a value that is influenced by other factors in addition to the state of existence of the ferromagnetic powder in the magnetic layer. [Industrial Applicability]
[0118] One aspect of the present invention is useful in the technical field of various magnetic recording media such as magnetic tapes for data storage.
Claims
1. A magnetic tape having a magnetic layer containing ferromagnetic powder on a non-magnetic support, The thickness of the magnetic layer is 20 nm or more and 90 nm or less, The absolute value ΔN of the difference between the refractive index Nxy measured in the in-plane direction of the magnetic layer and the refractive index Nz measured in the thickness direction of the magnetic layer is 0.25 or more and 0.40 or less, and A magnetic tape in which the logarithmic decrement of the surface of the magnetic layer as determined by a pendulum viscoelasticity test is 0.050 or less.
2. 2. The magnetic tape according to claim 1, wherein the difference between the refractive index Nxy and the refractive index Nz, Nxy-Nz, is 0.25 or more and 0.40 or less.
3. 3. The magnetic tape according to claim 1, wherein the logarithmic decrement is equal to or greater than 0.010 and equal to or less than 0.
050.
4. 4. The magnetic tape according to claim 1, further comprising a non-magnetic layer containing non-magnetic powder between the non-magnetic support and the magnetic layer.
5. 5. The magnetic tape according to claim 1, further comprising a backcoat layer containing a nonmagnetic powder on the surface of the nonmagnetic support opposite to the surface having the magnetic layer.
6. 6. The magnetic tape according to claim 1, wherein the non-magnetic support comprises at least one material selected from the group consisting of polyethylene terephthalate and polyethylene naphthalate.
7. A magnetic tape according to any one of claims 1 to 6, A magnetic head; A magnetic recording and reproducing apparatus comprising:
Citation Information
Patent Citations
Magnetic recording medium
JP2005243162A
Magnetic tape, and manufacturing method for the same
JP2017111841A
Magnetic tape and magnetic recording / reproducing apparatus
WO2019065199A1